TARI KELING GUNO JOYO SEBAGAI IDENTITAS KULTURAL MASYARAKAT MOJO, SINGGAHAN, PULUNG, PONOROGO - Yulia Anggraini S.A.B; Aulia Arifatuzzahro; Azzumrotul Marwah Al-ibrahimy; Intan Nur Kiptyah; Siti Nur Khasanah; Faridatul Hasanah; Vinka Tiara Pratiwi; Amroza Del Urba Azzahro (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
Tari Keling Guno Joyo is a traditional dance from Dusun Mojo, Singgahan Village, Pulung Subdistrict, Ponorogo Regency. This dance is not only entertainment but a symbol of cultural identity containing historical, customary, and mystical values. This study employs a qualitative descriptive method with an ethnographic approach to understand the philosophical meaning, historical values, and traditions inherent in Tari Keling. Data were collected through non-participant observation and in-depth interviews with traditional leaders, performers, and youth. The results show the dance represents togetherness, family values, and simplicity, serving as an educational and distinctive means of cultural preservation. This article aims to contribute to local cultural preservation and public understanding.